Prevalence and factors associated with access to contraceptive methods among Venezuelan immigrants in Peru. - Lopez-Gomero, Alicia María (2025)
Introduction: Access to contraceptive methods in Venezuelan immigrant women residing in Peru presents limitations due to multiple factors that directly impact their ability to obtain and use them. Objective: To describe the prevalence and explore the factors associated with the use of contraceptive methods among Venezuelan immigrant women in Peru during 2022. Methods: Cross-sectional analytical study of secondary data from the second Survey of the Venezuelan Population Residing in Peru (ENPOVE). The generalized linear Poisson model with log-link function was used and crude prevalence ratios (PRc) and adjusted prevalence ratios (PRa) were calculated with their respective 95% confidence intervals (95% CI). Results: The prevalence of access to contraceptive methods was 50%. Access to contraceptive methods was higher in those Venezuelan immigrant women who were young (PRa: 3.12; 95 % CI: 1.79 to 5.47), cohabitants (PRa: 2.39; 95 % CI: 2.05 to 2.78) and residents of Chiclayo (PRa: 1.24; 95 % CI: 1.07 to 1.44), but was lower in those who were not heterosexual (PRa: 0.62; CI: 0.41 to 0.93), entered Peru during the years 2020 to 2022 (PRa: 0.82; CI: 0.74 to 0.91) and presented a need for access to health services (PRa: 0.87; CI: 0.80 to 0.93). Conclusion: One out of two Venezuelan immigrant women accessed contraceptive methods. Factors such as youth, living with a partner and residing in Chiclayo were associated with greater access, while not being heterosexual, entering Peru between 2020 and 2022 and having a need for access to health services were associated with less access to contraceptive methods.